2013
DOI: 10.1186/2050-2974-1-29
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anorexia nervosa: an overview of universal issues and contextual challenges

Abstract: AimAnorexia Nervosa (AN) is a complex and clinically challenging syndrome. Intended for specialist audiences, this narrative review aims to summarise the available literature related to assessment in the adult patient context, synthesising both research evidence and clinical consensus guidelines.MethodWe provide a review of the available literature on specialist assessment of AN focusing on common trajectories into assessment, obstacles accessing assessment, common presenting issues and barriers to the assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 115 publications
2
10
0
Order By: Relevance
“…The scales on which the Low Pathology AN patients reported clinical elevations, including Interpersonal Problems, were typical of the scores expected in this clinical sample according to EDI-3 norms, and suggest that these patients experience some level of distress in social relationships, feelings of insecurity, and generally poor interpersonal relationships (Garner, 2004). The characteristics of the Low Pathology AN patients may support the potential effects of the AN symptoms, in that as the disorder progresses and weight drops individuals' fear of fatness may also decrease as they are not confronted with as much fat on their body (Sugenor & Maguire, 2013).…”
Section: Summary Of the Low Pathology An Subtypementioning
confidence: 94%
“…The scales on which the Low Pathology AN patients reported clinical elevations, including Interpersonal Problems, were typical of the scores expected in this clinical sample according to EDI-3 norms, and suggest that these patients experience some level of distress in social relationships, feelings of insecurity, and generally poor interpersonal relationships (Garner, 2004). The characteristics of the Low Pathology AN patients may support the potential effects of the AN symptoms, in that as the disorder progresses and weight drops individuals' fear of fatness may also decrease as they are not confronted with as much fat on their body (Sugenor & Maguire, 2013).…”
Section: Summary Of the Low Pathology An Subtypementioning
confidence: 94%
“…As highlighted in our original study (Worsfold & Sheffield, 2018), various gaps still exist within ED‐MHL research (Linville et al, 2012; Mond, 2014; Surgenor & Maguire, 2013). First, research could extend past exploring beliefs and practices of medical professionals to a broader group of health practitioners that are regular providers of mood or weight management services, such as psychologists, naturopaths and fitness instructors.…”
Section: Introductionmentioning
confidence: 96%
“…Early diagnosis and intervention has prognostic benefits in limiting the ED’s progression and improving physical and psychosocial outcomes [13, 14]. EDs are clinically challenging for mental health services due to the high medical risks brought on by the disorder [15]. It is commonly reported that health professionals from various clinical disciplines lack confidence and training in screening, diagnosing and treating people with EDs [1618].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of training, experience, and inadequate educational resources have also been associated with negative attitudes of health professionals towards people presenting with an ED [15]. These negative or dismissive perceptions are likely related to the nature of the symptoms and blame-based stigmatisation [2628].…”
Section: Introductionmentioning
confidence: 99%